2018
DOI: 10.13004/kjnt.2018.14.2.159
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Posterior Inferior Cerebellar Artery Infarction after Cervical Chiropractic Manipulation

Abstract: We describe the case of a patient who had infarction of the posterior inferior cerebellar artery (PICA) after a chiropractic cervical manipulation. A 39-year-old man visited the emergency room with signs of cerebellar dysfunction, presenting with a 6-hour history of vertigo and imbalance. Two weeks ago, he was treated by a chiropractor for intermittent neck pain. At the time of admission, brain computed tomography, magnetic resonance imaging, and angiography revealed an acute infarction in the left PICA territ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…Although patients with PICA dissection tended to hemorrhage compared with ischemia 94 , Junpei et al still found that isolated PICA dissection caused 6% of the PICA region infarcts by reviewing 167 cases, equal to VA dissection, which hinted the undervalued clinical importance of PICA dissection 95 . Jeong et al reported a rare case of PICA infarct after cervical chiropractic manipulation 96 . Extradural origin of PICA could be injured accidently by the cervical surgery 97 .…”
Section: Ischemic Strokementioning
confidence: 99%
“…Although patients with PICA dissection tended to hemorrhage compared with ischemia 94 , Junpei et al still found that isolated PICA dissection caused 6% of the PICA region infarcts by reviewing 167 cases, equal to VA dissection, which hinted the undervalued clinical importance of PICA dissection 95 . Jeong et al reported a rare case of PICA infarct after cervical chiropractic manipulation 96 . Extradural origin of PICA could be injured accidently by the cervical surgery 97 .…”
Section: Ischemic Strokementioning
confidence: 99%
“…These do not appear to be minor adverse effects, even if they did resolve by 24 hours. But Gergen and Jeong [ 21 , 22 ] reported infarction of the posterior inferior cerebellar artery and mild traumatic brain injury (mTBI) which occurred likely because of shedding of the thrombus after manual therapy. Therefore, it is essential for the physical therapist to evaluate the risks before initiating treatment.…”
Section: Evidence Synthesismentioning
confidence: 99%
“…In the literature, several cases of infarction have been reported after chiropractic therapy and, to a lesser extent, after self-cervical manipulation. And all of these cases are associated with vascular pathologies [5][6][7][8] .…”
Section: Introductionmentioning
confidence: 99%